Estimates of flour and starch yield of cassava roots - Pola, Augusto Carlos (2021)
Through linear regression analysis, equations and graphs were developed that allow estimates of flour yield for the Sul Catarinense and Vale do Itajaí regions, in Santa Catarina, Brazil. In another linear regression study, a mathematical model was generated to estimate the starch yield of the roots from their dry matter content. The method used showed a starch extraction efficiency of 66%, that is, about one third of the starch was retained in the residue. Considering an industrial extraction efficiency close to this value, it is possible to use the equation generated to estimate the production of industrial starch yield from the dry matter content of the tubers. The contents of dry matter and starch of the roots of five commercial cassava cultivars in the south of Santa Catarina, harvested after one and two vegetative cycles, were also determined in this work. Average increases of 8.4% and 5.1% percentage points were recorded in the dry matter content and in the starch yield at the end of the second cultivation cycle.